L’errance, un mouvement à potentiel utopique - Emilie Ieven (Carnets)
This paper aims to enlighten the utopian power of wandering which creates new connections and relations with and inside space. For this purpose, this analysis will defend a new definition of the term of wandering itself, based on the etymology of the word as well as on the philosophy of Deleuze and Guattari. By focusing on three of Jean Echenoz's novels (Un An, Le Méridien de Greenwich, Les Grandes blondes), this paper will finally demonstrate the specific utopian power of wandering which confers to the contemporary character new ways to elaborate and respond to spatial issues.